A Framework to Harmonize Legal Provisions in Infrastructure PPP Projects in Egypt Funded by Multilateral Development Banks - ElKadi, Menna (AUC Knowledge Fountain, 2025)
Over the last decade, Egypt has witnessed an increase in the number of Public-Private Partnership (PPP) projects, specifically in infrastructure, as a result of the growing interest and popularity of various entities participating in such projects. Public infrastructure systems are no longer thought to be exclusively provided by the government; instead, the private sector’s contribution in the provision of such services is increasing. However, not every PPP program has been equally effective or has made the optimum use of planning and decision-making. The possibility of a project failure as a result of poor risk allocation is increased, if the potential dispute causing factors are not taken into account, and correspondingly acted upon. This research aims to develop a framework for best practices focusing on the alignment of legal provisions in Infrastructure projects funded by Multilateral Development Banks, aiding all project entities to address their diversified purposes, to optimize each entity’s objectives and resolve conflicts up front, with consideration to legal aspects. This was accomplished by addressing the three main contractual relationships; concession agreement, lending agreement, and engineering, procurement and construction (EPC) agreement, focusing on the most crucial contract provisions that have the potential of causing conflicts between parties, namely; (1) governing law and (2) dispute resolution in both the concession and EPC agreements of five real-world case studies in addition to expert interviews. Multilateral Development Banks were found to have relatively high preference in regards to the choice of English law as the governing law of lending and EPC agreements. It can be concluded that having different governing laws in the agreements would not affect the success of the project, However, the selection of the legal provisions to be applied is crucial. Moreover, in regards to dispute resolution, conflicts cause delays, which lead to higher costs. Therefore, the effectiveness of the dispute settlement process is important in luring Multilateral Development Banks and private investors to collaborate with the government.